Proposing an Electronic System for Following-up and Managing the Field Training: Palestine Ahliya University as a Case: نظام إلكتروني مقترح لمتابعة وإدارة التدريب الميداني في جامعة فلسطين الأهلية: دراسة حالة - Sameh Taqatqa, Ahmad Hasasneh, Jamil Itmazi (Journal of engineering sciences and information technology, 2019)
Obviously, digital technology offers simplified solutions to solve or mitigate problems in general. In the academic sector in particular, the field training is one of the core courses that students must enroll during the third and fourth academic year, where the students have manually to select a relevant organization or institution based on their specialization. The academic staff and hosting institutions do not supervise the trainees as required due to lack of communication between them, wrong selection of the hosting institutions by students in some cases, limited following-up the trainees, thus leading to uncertainty in the number of training hours and reports required by students. These problems can be addressed or mitigated by proposing an electronic training system improving the communication between supervisors of field training, host institutions, and trainees and thus solving most of the mentioned problems. Based on this e-training system, the training unit at the university could therefore follow-up the trainees and thus improve the communication and cooperation with the training institutions. It will also definitely contribute in improving the training task itself for the students. In this proposed paper, the importance of the proposed system was presented. Other related systems were mentioned and used as references in the analysis stage. In the analytical stage, data was collected using 3 different questionnaires developed for students, supervising staff, and for the training institutions. Consequently, obstacles and problems faced these entities were extracted and mentioned. Finally, a preliminary design was proposed in this paper to develop and implement an electronic training system at Palestine Ahliya University.